Modulation of γδ T-cell activation by neutrophil elastase - Towstyka, Nadia Yasmín (2017)
γδ T cells are non-conventional, innate-like T cells, characterized by a restricted T-cell receptor repertoire. They participate in protective immunity responses against extracellular and intracellular pathogens, tumour surveillance, modulation of innate and adaptive immune responses, tissue healing, epithelial cell maintenance and regulation of physiological organ function. In this study, we investigated the role of neutrophils during the activation of human blood γδ T cells through CD3 molecules. We found that the up-regulation of CD69 expression, and the production of interferon-γ and tumour necrosis factor-α induced by anti-CD3 antibodies was potentiated by neutrophils. We found that inhibition of caspase-1 and neutralization of interleukin-18 did not affect neutrophil-mediated modulation. By contrast, the treatment with serine protease inhibitors prevented the potentiation of γδ T-cell activation induced by neutrophils. Moreover, the addition of elastase to γδ T-cell culture increased their stimulation, and the treatment of neutrophils with elastase inhibitor prevented the effect of neutrophils on γδ T-cell activation. Furthermore, we demonstrated that the effect of elastase on γδ T cells was mediated through the protease-activated receptor, PAR1, because the inhibition of this receptor with a specific antagonist, RWJ56110, abrogated the effect of neutrophils on γδ T-cell activation.